Ceaseless Power Generation from Renewable Energy in India - Mishra, Monalisha (Digital Repository of Theses - SSBM Geneva, 2025)
The global energy landscape is undergoing a pivotal transformation, driven by the need to address environmental concerns and mitigate climate change. Renewable energy, particularly solar power, is increasingly recognized as essential to meeting the escalating global energy demand and overcoming the limitations of fossil fuels. In line with international agreements such as the Paris Agreement, which aims to limit global temperature rise to 1.5°C, the transition from fossil-based to renewable-based energy systems is a critical priority. This thesis explores the objective of ceaseless power generation from renewable energy sources in India, focusing on overcoming the technical, financial, and policy barriers that hinder the large-scale deployment of renewable energy. The research draws upon my six years of experience as an Engineering Manager in the renewable energy sector, where I have developed a passion for advancing clean energy technologies. By focusing on hybrid renewable energy systems, this research aims to provide practical solutions for uninterrupted power generation, tailored to India's unique energy landscape. The research employs a combination of qualitative and quantitative methods to address key challenges. Through policy analysis and interviews with stakeholders, the study evaluates the current regulatory frameworks and financial constraints. Case studies of successful renewable energy projects are analyzed to identify best practices, while geospatial data and survey results are used to assess the renewable energy potential and community impacts. Advanced statistical techniques, such as correlation and regression analysis, are employed to model the impact of financial and technical barriers on renewable energy deployment. The findings of this research aim to inform the development of a comprehensive framework for sustainable, continuous power generation from renewable sources in India. The results provide insights into cost reduction, energy security, and grid integration, with actionable strategies for policymakers, investors, and industry professionals. By offering a techno-commercially optimized solution, this thesis contributes to both industry practice and the broader global efforts to combat climate change. In conclusion, this research represents a critical step toward achieving a sustainable energy transition in India, addressing real-world challenges, and offering viable solutions for ceaseless renewable energy generation.